2021
DOI: 10.3390/pharmaceutics13060841
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Capsaicin Loaded Nanocrystals: Physical Characterizations and In Vivo Evaluation

Abstract: Nano-crystallization is a new emerging strategy to promote the saturation solubility, dissolution rate and subsequent bioavailability of Biopharmaceutical Class II drugs. Capsaicin belongs to BCS class-II drugs having low water solubility and dissolution rate. Nano-crystals (NC) of pure Capsaicin was developed and optimized in order to increase its water solubility, dissolution and further to promote its adhesiveness to skin epidermis layer. NC formulations were subjected to stability studies, droplet size, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The XRD pattern indicates that the synthesized sample is in the nanoscale range. In addition, the diffraction peaks at 20.25 o and 28.0° corresponded to Capsaicin 44 , confirming the loading of capsaicin with the synthesized CoFe 2 O 4 NPs. The crystallite size of the synthesized NPs was caculated using Scherrer’s Equation 45 : where, D is the crystallite size, λ is the X-ray wavelength used, β is the full width at half maximum (FWHM) and θ is the diffraction angle.…”
Section: Resultsmentioning
confidence: 52%
“…The XRD pattern indicates that the synthesized sample is in the nanoscale range. In addition, the diffraction peaks at 20.25 o and 28.0° corresponded to Capsaicin 44 , confirming the loading of capsaicin with the synthesized CoFe 2 O 4 NPs. The crystallite size of the synthesized NPs was caculated using Scherrer’s Equation 45 : where, D is the crystallite size, λ is the X-ray wavelength used, β is the full width at half maximum (FWHM) and θ is the diffraction angle.…”
Section: Resultsmentioning
confidence: 52%
“…Chitosan and its derivatives (i.e., CMCS) could be used in pesticide delivery, copolymeric concentration, and nanomicellar, which could effectively prevent ecological harm, including the photodegradation of the active ingredients [ 51 ]. In addition, chitosan could give the CAP loaded in microcapsules good solubility and permeation into the insect gut, causing a series of adverse reactions, such as delayed growth and development, decreased adult weight and reproduction rate, and even death [ 49 , 52 ]. This experiment further suggested that the CAP could significantly disturb the growth and development of the insects.…”
Section: Discussionmentioning
confidence: 99%
“…Solution (1 mL) was taken, and PBS was used to dilute it up to 10 mL (pH 6.8). Using a UV-Visible Spectrophotometer at 273 nm, the drug content in emulgel was calculated spectrophotometrically (22,23). To determine the homogeneity of the drug content, experiments are carried out in triplicate (n = 3).…”
Section: Determination Of Drug Contentmentioning
confidence: 99%